Scoping review of evidence synthesis: Concepts, types and methods. - Carla Andrea Trapé; Célia Maria Sivalli Campos; Cintia de Freitas Oliveira; João Gabriel Sanchez Tavares da Silva; Liza Yurie Teruya Uchimura; Mabel Fernandes Figueiró; Maritsa Carla de Bortoli; Sidney Marcel Domingues; Tatiana Yonekura (PLoS ONE)
Objectives To systematically explore the concepts, types, and methodologies related to literature reviews and evidence synthesis. Methods We conducted a scoping review using PubMed, Embase, Biblioteca Virtual da Saúde, grey literature, and websites of key international and national institutions, including the Cochrane Collaboration, Joanna Briggs Institute, Center for Reviews and Dissemination, Campbell Collaboration, and REBRATS, with searches completed through November 13, 2024. Studies were included if they identified or proposed theories and/or methodologies for evidence synthesis at international or national levels, with eligibility limited to studies published in English, Spanish, or Portuguese and no restrictions on publication year. Title and abstract screening was conducted independently by ten reviewers working in pairs, with a third reviewer resolving conflicts as needed, and full-text copies of potentially relevant articles were retrieved for further analysis. Results The review included 99 studies employing a variety of evidence synthesis methods. A total of 71 terminologies for types of evidence synthesis were identified and grouped by conceptual and methodological similarities, resulting in 16 categories of evidence synthesis, each with clear differences in concepts and methods. Conclusions The lack of standardization in defining and classifying review types challenges the scientific community by hindering study comparisons and appropriate methodology selection. Future research should explore the relationships between different review types and their outcomes, as well as the applicability of new methodologies across various fields.